Potential assessment of using dry cooling mode in two different solar thermal power plants. - Taqiy Eddine Boukelia (International Journal of Energetica)
Most of Concentrating Solar Power (CSP) plants are usually installed in desert regions where water resource availability is a critical limitation due to the lack of water required for the exploitation of these systems in these regions. Therefore, the aim of this study is to investigate the techno-economic competitiveness of deploying both modes of cooling (wet and dry) in two different parabolic trough solar thermal power plants integrated with thermal energy storage and fuel backup system; the first one is using thermic oil, while the other is working using molten salt. The obtained results show that the dry cooling mode can decrease the yields of the two power plants down to 8.7 % and 9.3 % for oil and salt configurations respectively. On the other hand, the levelized cost of electricity can increase by using this cooling option up to 9.3 % for oil plant, and 10.0 % for salt one. However, the main advantage of using dry cooling option is reducing water consumption which has been decreased by more than 94 % for both plants. The application of our methodology to other two sites worldwide, confirms the viability of the obtained results. The importance of this results is to show the effect of working fluids on the cooling system of solar power plants.